2020
DOI: 10.1002/mc.23194
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cathepsin D (CTSD) enhances radiosensitivity of glioblastoma cells by attenuating autophagy

Abstract: Postoperative radiotherapy combined with chemotherapy is a commonly used treatment for glioblastoma (GBM) but radiotherapy often fails to achieve the expected results mainly due to tumor radioresistance. In this study, we established a radioresistant subline from human glioma cell line U251 and found that Cathepsin D (CTSD), a gene closely related to the clinical malignancy and prognosis in glioma, had higher expression level in radioresistant clones than that in parental cells, and knocking down CTSD by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Our previous work has successfully established a radioresistant cell line (named as U251R) from human glioma U251 cells and issued the DEGs between U251 and U251R cells by TMT quantitative proteomic analysis [ 18 ]. To know much more genes precisely involved in the radioresistance of GBM, here we further explored the DEGs between U251 and T98G cells by TMT analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has successfully established a radioresistant cell line (named as U251R) from human glioma U251 cells and issued the DEGs between U251 and U251R cells by TMT quantitative proteomic analysis [ 18 ]. To know much more genes precisely involved in the radioresistance of GBM, here we further explored the DEGs between U251 and T98G cells by TMT analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Human glioblastoma cell lines of U251 and T98G were purchased from Cell Bank of Chinese Academy of Science. The stable U251R cell line was previously developed from its parental cell line U251 by exposing it with 2 Gy X-ray/day for 30 fractions (5 fractions/weekly in general) with a total dose of 60 Gy [ 18 ]. U251 and U251R cells were cultured in DMEM medium (Gibco, Thermo Fisher Scientific, Waltham, MA, USA), and T98G cells were cultured in MEM medium (Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that CTSD might be a useful GBM marker and predictor of prognosis. Moreover, in vitro studies have shown that the manipulated inhibition or promotion of CTSD expression modulates apoptosis, proliferation, invasiveness, migration ability, and autophagy level to affect the radio-sensitivity of glioma cells [ 21 , 22 , 23 ]. Our results found that migration and invasion significantly inhibition of si-Control-LCN2 or si-CTSD-Neo treatment upon LCN2 overexpressing GBM cells, but not completely inhibition of CTSD protein expression ( Figure 5 D).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of cathepsin D (CTSD) is reported to correlate with a poor prognosis in esophageal squamous cell carcinoma and malignant glioma [ 17 , 18 , 19 ]. The importance of CTSD in malignant glioma invasion was demonstrated using mass spectrometry analysis [ 20 ] and under- or over-expression of CTSD modulated the malignant potential and radio-sensitivity of glioma cells [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the downregulation of cathepsin L is likely responsible for the radiosensitivity effect of TFP ( 102 ). Zheng et al found that the inhibition of cathepsin D (lysosomal aspartyl protease) by its inhibitor or siRNA attenuated autophagy and enhanced the radiosensitivity in U251 cell lines ( 103 ). Taken together, the combination of autophagy inhibitors and radiotherapy showed promising effectiveness, by increasing the sensitivity and enhancing cell apoptosis.…”
Section: Prospect-targeting Autophagy In Glioblastoma Therapymentioning
confidence: 99%